The Accelerated Benefits Demonstration: Impacts on the Employment of Disability Insurance Beneficiaries - Bailey, Michelle Stegman; Weathers, Robert R. (American Economic Review, 2014)
We use data from the Accelerated Benefits demonstration to estimate the impacts of providing newly entitled disability insurance (DI) beneficiaries with health insurance and additional services during the DI program's 24-month Medicare waiting period. While health insurance alone did not increase employment, the additional employment services appeared to have positive short-term impacts on labor market activity. We find a statistically significant increase in employment and earnings in the second calendar year after random assignment; although these findings disappear in the third calendar year. Our results may have implications for disability reform proposals and provisions within the Affordable Care Act.